Both Light Intensity and Moderate‐to‐Vigorous Physical Activity Measured by Accelerometry Are Favorably Associated With Cardiometabolic Risk Factors in Older Women: The Objective Physical Activity and Cardiovascular Health (OPACH) Study. Issue 10 (17th October 2017) - LaMonte, Michael J.; Lewis, Cora E.; Buchner, David M.; Evenson, Kelly R.; Rillamas‐Sun, Eileen; Di, Chongzhi; Lee, I‐Min; Bellettiere, John; Stefanick, Marcia L.; Eaton, Charles B.; Howard, Barbara V.; Bird, Chloe; et al.
Abstract : Background: The relationship between light intensity physical activity (PA), which is common in older adults, and cardiovascular disease (CVD) risk factors is unclear. This study examined associations of accelerometer‐measured PA intensity with CVD risk factors in older women of different race‐ethnicities. Methods and Results: Cross‐sectional analyses were conducted in 4832 women (mean age 78.9 years; 52.5% white, 30.5% black, 17.1% Hispanic) who were without known CVD and wore triaxial accelerometers a minimum of 4 of 7 days with ≥10 hours/d awake wear‐time. Vector magnitude counts per 15‐s epoch were used to define time spent in low light (19–225 counts/15 s), high light (226–518), and moderate‐to‐vigorous; ≥519) intensity PA. Fasting CVD biomarkers, resting blood pressure, waist girth, body mass index, and 10‐year predicted CVD risk (Reynolds Risk Score) were measured. After adjusting for age, wear time, race‐ethnicity, and potential confounders, each PA measure was favorably associated with mean high‐density lipoprotein, triglyceride, glucose, C‐reactive protein, body mass index, waist girth, and Reynolds Risk Score ( P <0.05, all). Associations with mean blood pressure, insulin, and total and low‐density lipoprotein cholesterol were variable. A 30‐minute/d increment in PA was associated, on average, with odds ratios for high predicted CVD risk (Reynolds Risk Score ≥20) of 0.96 (95% confidence interval, 0.92, 1.00), 0.88 (0.83, 0.94), and 0.85 (0.79, 0.91) for low light, high light, and moderate‐to‐vigorous, respectively, and remained significant with further mutual control for PA intensity. Conclusions: PA measured by accelerometry, including light intensity PA, was associated with lower CVD risk factor levels in race‐ethnically diverse older women.